Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/mnras/stw042
|View full text |Cite
|
Sign up to set email alerts
|

A search for white dwarfs in the Galactic plane: the field and the open cluster population

Abstract: We investigated the prospects for systematic searches of white dwarfs at low Galactic latitudes, using the VLT Survey Telescope H α Photometric Survey of the Galactic plane and Bulge (VPHAS+). We targeted 17 white dwarf candidates along sightlines of known open clusters, aiming to identify potential cluster members. We confirmed all the 17 white dwarf candidates from blue/optical spectroscopy, and we suggest five of them to be likely cluster members. We estimated progenitor ages and masses for the candidate cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…We note that observations of ultra-massive 20 white dwarfs are particularly difficult due to their relative scarcity, inherently low luminosity due to more compact nature, as well as more rapid cooling (Althaus et al, 2007). Recent works by Cummings et al (2016a,b) and Raddi et al (2016) have derived semi-empirical initial-final mass relations for ultramassive WDs using observations from young open clusters. However, the procedure to derive an initial-final mass relation is quite involved and is affected by quite a range of uncertainties.…”
Section: Low Mass Channelmentioning
confidence: 94%
“…We note that observations of ultra-massive 20 white dwarfs are particularly difficult due to their relative scarcity, inherently low luminosity due to more compact nature, as well as more rapid cooling (Althaus et al, 2007). Recent works by Cummings et al (2016a,b) and Raddi et al (2016) have derived semi-empirical initial-final mass relations for ultramassive WDs using observations from young open clusters. However, the procedure to derive an initial-final mass relation is quite involved and is affected by quite a range of uncertainties.…”
Section: Low Mass Channelmentioning
confidence: 94%
“…Reimers & Koester (1989) discovered seven white dwarf candidates on photographic plates of which three could be verified spectroscopically (Koester & Reimers 1993). More recently Dobbie et al (2009Dobbie et al ( , 2012 have confirmed further white dwarfs and Raddi et al (2016) have discovered an additional candidate. Having seven confirmed white dwarf members makes NGC 3532 a rich source for degenerate objects among Galactic open clusters (Dobbie et al 2012), further testifying to its value for studies of stellar evolution.…”
Section: Introductionmentioning
confidence: 95%
“…Within the past 10 years, the increasing availability of both widefield imagers and spectrographs on large telescopes has led to a significantly increased number of known white dwarfs in star clusters. This includes the work of Kalirai et al (2005Kalirai et al ( , 2008Kalirai et al ( , 2009), Williams et al (2009), Casewell et al (2009, Dobbie et al (2009Dobbie et al ( , 2012, Cummings et al (2015Cummings et al ( , 2016aCummings et al ( , 2016b hereafter Papers I, II, and III, respectively), and Raddi et al (2016).…”
Section: Introductionmentioning
confidence: 99%